Akibat Hukum Terhadap Orang Tua yang Tidak Menjalankan Putusan Hak Asuh Anak Berdasarkan Hukum Perdata di Indonesia - Syailendra P, Moody Rizqy; Madelin, Nethania Aurelia; Nathania, Cheryl; Maulika, Grizca Ratu (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Marriage in Indonesia, regulated by Undang - Undang Number 1 of 1974, aims to create a happy family; however, divorce often triggers custody disputes. This research analyzes the implementation of sanctions for parents who do not comply with child custody decisions within the context of civil law, as well as the obstacles faced in its execution. The methods used include normative and qualitative approaches, with data sources from legislation and case studies. Real cases, such as disputes between Tsania Marwa and Atalarik Syah, as well as Ahmad Dhani and Maia Estianty, highlight non-compliance with legal decisions. Obstacles such as weak law enforcement, economic factors, and social norms contribute to this issue. Ongoing conflicts between parents further worsen the situation. Therefore, reform in law enforcement and increased social awareness regarding child custody are essential to protect children's welfare and ensure more effective implementation of court decisions, so that the best interests of the child always remain a priority in every decision.